Immediate Loading of Single Implant in the Aesthetic Zone: A Case Report (Academia Journal of Medicine, 2024)
An implant-supported restoration in the anterior zone  must produce the best possible aesthetic outcome.  Providing rapid interim restorations after implant surgery  has been suggested as a preferable course of therapy in  the aesthetic zone. Following implant implantation, a well contoured interim restoration reduces alterations to the  hard and soft tissues surrounding the implant. The  aesthetic result and, thus, patient satisfaction may be  improved as a result. To get the desired outcome, several  prosthetic and surgical components must be properly  designed and carried out. This case report describes the immediate loading of a single implant in the aesthetic  zone.
Keywords: Immediate loading; prosthetic rehabilitation; primary stability; bone density; interim restoration